Gunk-eyed Literature: memory in the novels O mendigo que sabia de cor os adágios de Erasmo de Rotterdam, and Nunca houve tanto fim como agora, by Evandro Affonso Ferreira - Andrade, Maria Regina Soares Azevedo de; Welter, Juliana Vargas (Revista Letras Raras, 2022)
This work aims to investigate the memory feature in contemporary Brazilian Literature in the novels “O mendigo que sabia de cor os adágios de Erasmo de Rotterdam” (2012) and “Nunca houve tanto fim como agora” (2017), both written by Evandro Affonso Ferreira. For this purpose, the theoretical references on memory were based on the works of Candido (2006), Gagnebin (2006), Halbwachs (2004), Ricoeur (2007), Sarlo (2007) and Schollhammer (2007). Candido (2006) states that literature and society are inseparably connected, as the former is interwoven with representations of the latter. Therefore, the hypothesis is that the recurrence of the memory feature characterizes a Brazilian literature that remembers through writing, given the need to account for a violent and unsolved past. Finally, by analyzing the aforementioned literary works, it is possible to verify that the use of memory is a means to reclaim other versions of History, bringing up individuals and narratives made invisible historically.